The effect of arginine on root system development in Norway spruce (Picea abies L. Karst) somatic embryos - Carlsson, Johanna (SLU/Dept. of Forest Genetics and Plant Physiology, 2012)
The demands for higher production yields and better quality materials from the forests are increasing globally. Tree breeding programs are directed to meet the future demands on forests. In order to capture the full benefits from the breeding programs, clonal propagation is necessary. For most conifer species, somatic embryogenesis (SE) is the only available option for large scale clonal propagation of Elite clonal material. For Norway spruce (Picea abies L. Karst.), SE procedures suitable for laboratory scale propagation have been available since the mid-1980s. The SE technique has a great potential for mass propagation of conifer species; however the implementation in forestry for plant production has so far been hampered by the labor intensive procedures making the technique costly. SE involves a series of developmental processes, starting with induction of embryogenic cultures from an initial explant, multiplication of somatic embryos in the proliferation phase, early embryo differentiation, maturation and germination.